Natural Bioactive Compounds and Human Health (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
"Natural Bioactive Compounds and Human Health" comprehensively explores the profound impact of natural substances on human well-being. From phytochemicals and antioxidants to polyphenols and beyond, this reprint delves into how these compounds, derived from plants, fungi, marine organisms, and more, contribute to health and disease prevention. Featuring contributions from experts across disciplines, it bridges traditional knowledge with modern scientific research to uncover their roles in combating chronic diseases, enhancing immune function, and promoting overall vitality. This volume serves as an invaluable resource for researchers, healthcare professionals, and anyone intrigued by the therapeutic potential of nature's bioactive compounds.